Modifications in magnetic anisotropy of M-type strontium hexaferrite crystals by swift heavy ion irradiation - Kaur, Balwinder; Bhat, Monita; Licci, F.; Kumar, Ravi; Kulkarni, S. D.; Joy, Pattayil Alias; Bamzai, K. K.; Kotru, P. N. (Journal of Magnetism and Magnetic Materials, 2006)
Using vibrating sample magnetometery (VSM) 50 MeV Li(3+) ion irradiation effects on magnetic properties of single crystals of SrGa(x)In(y)Fe(12-(x+y))O(19) (where x = 0, 5, 7, 9; y = 0, 0.8, 1.3, 1.0), are reported. The substitution of Ga and In in strontium hexaferrite crystals decreases the value of magnetization sharply, which is attributed to shifting of collinear magnetic order to a non-collinear one. Reduction of magnetization is also explained to be as a result of the occupation of the crystallographic sites of Fe(3+) by Ga(3+) and In(3+). The Li(3+) ion irradiation decreases the value of magnetization, irrespective of whether the crystals are Ga-In substituted or unsubstituted crystals of SrFe(12)O(19). The result is interpreted in terms of the occurrence of a paramagnetic doublet in crystals replacing magnetic sextuplet as a result of irradiation. Substitution of Ga-In in Strontium hexaferrite decreases the value of anisotropy constant. Irradiation with Li(3+) ions increases the values of anisotropy field for both substituted as well as unsubstituted crystals. Substitution with Ga-In also decreases the Curie temperature (T(c)) but the irradiation with Li(3+) ions does not affect the curie temperature of either Ga-In substituted or pure SrFe(12)O(19) crystals. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: anisotropy field; Curie temperature; irradiation; Magnetic anisotropy; Magnetization

Synthesis of La0.7Sr0.3MnO3 at 800 degrees C using citrate gel method - Ravi, V.; Kulkarni, S. D.; Samuel, V.; Kale, Sangeeta N.; Mona, J.; Rajgopal, R.; Daundkar, A.; Lahoti, P. S.; Joshi, Rakesh S. (Ceramics International, 2007)
Manganite systems have been of considerable interest in the recent past due to their potential to operate in wide property range and also to serve as effective magnetic sensing and storing devices when synthesized using stringent conditions. We report a novel citrate gel method, in which La0.7Sr0.3MnO3 system has been synthesized at temperature 800 degrees C (LSMO800) with the synthesis duration is 6 h. The results have been compared with the sample synthesized at 1050 degrees C (LSMO1050). The synthesized bulk polycrystalline sample shows single-phase nature with the increase in particle size from similar to 50 nm to 300 nm with the increase in the sintering temperature. The magnetization data for LSMO800 shows well-defined hysteresis with saturation magnetization at around 1800 Oe and Curie temperature at 360 K, which is slightly lower than that of LSMO1050, which is 375 K. The results can be well attributed to the grain boundary effects. (C) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Citrate gel method; CMR; Oxides

Anomalous microwave heating effects in Ce-doped La(0.7)Sr(0.3)MnO(3): possible role of grain boundary capacitative effects across cerium solubility limit - Kale, Sangeeta N.; Mona, J.; Lofland, S. E.; Kulkarni, S. D.; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
Ce-doped manganite bulk nanocompacts [La(0.7-x)Ce(x)Sr(0.3)MnO(3) (0 < x < 0.1)] are studied for their microwave heating properties at 2.45 GHz. The heating effect is found to be nonmonotonic as a function of cerium concentration, and anomalously large heating (burning) is observed for a small concentration window near x=0.03. The x-ray diffraction studies show signatures of CeO(2) phase in x>0.03 samples. The various characterizations collectively point to the key role of the developing grain boundary CeO(2) layer which leads to highest capacitative intergrain-coupling and related charging-discharging effects when it is thinnest near the apparent Ce solubility limit of x similar to 0.03. (c) 2008 American Institute of Physics.

Enhanced shape anisotropy and magneto-optical birefringence by high energy ball milling in NixFe1-xFe2O4 ferrofluids - Nair, Swapna S.; Xavier, Francis; Joy, Pattayil Alias; Kulkarni, S. D.; Anantharaman, Maliemadom R. (Journal of Magnetism and Magnetic Materials, 2008)
Ferrofluids belonging to the series NixFe1-xFe2O4 were synthesised by two different procedures-one by standard co-precipitation techniques, the other by co-precipitation for synthesis of particles and dispersion aided by high-energy ball milling with a view to understand the effect of strain and size anisotropy on the magneto-optical properties of ferrofluids. The birefringence measurements were carried out using a standard ellipsometer. The birefringence signal obtained for chemically synthesised samples was satisfactorily fitted to the standard second Langevin function. The ball-milled ferrofluids showed a deviation and their birefringence was enhanced by an order. This large enhancement in the birefringence value cannot be attributed to the increase in grain size of the samples, considering that the grain sizes of sample synthesised by both modes are comparable; instead, it can be attributed to the lattice strain-induced shape anisotropy(oblation) arising from the high-energy ball-milling process. Thus magnetic-optical (MO) signals can be tuned by ball-milling process, which can find potential applications. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: birefringence; Co-precipitation; ferrofluid; HEBM

Complex permeability studies of Ni-Co-Zn ferrites synthesized by an oxalate precursor method - Ghodake, J. S.; Kambale, R. C.; Kulkarni, S. D.; Sawant, S. R.; Suryavanshi, S. S. (Smart Materials & Structures, 2009)
Nanocrystalline Co-substituted Ni-Zn ferrites have been synthesized by employing a co-precipitation technique using oxalate precursors. The co-precipitated oxalates were decomposed in air at 650 degrees C for 1 h and the powder was sintered at 1000 degrees C. The phase formation of the sintered ferrite was confirmed by x-ray diffraction studies. The lattice parameter a (angstrom) increases with the addition of Co(2+) which is attributed to the large ionic size of Co(2+) (0.78 angstrom), which replaces Ni(2+) (0.74 angstrom). The crystallite size has been estimated by the Debye-Scherrer formula using the full width at half-maximum (FWHM) of the line broadening of the (311) reflection and it is found to be in the range of 25-28 nm. Also, with increasing cobalt content the magnetocrystalline anisotropy constant (K(1)) and magnetostriction constant (lambda(s)) increase, and the grain size decreases, hence the value of initial permeability mu(i) decreases. The saturation magnetization M(s) and magnetic moment (n(B)) do not show any significant variation for all compositions varying with the cobalt content.

Microwave dielectric and attenuation properties of Ni0.7-xCoxZn0.3Fe2O4 thick films - Rendale, M. K.; Kulkarni, S. D.; Puri, Vijaya (Microelectronics International, 2009)
Purpose - The aim of this paper is to investigate permittivity of nano structured Ni0.7-xCoxZn0.3Fe2O4 thick films at microwave frequencies. Design/methodology/approach - Nanosized Ni0.7-xCoxZn0.3Fe2O4 ferrites with x = 0, 0.04, 0.08 and 0.12 were prepared by sucrose precursor technique using the constituent metal nitrates. Thick films of the ferrites were fabricated on alumina substrates by screen-printing technique. Microwave dielectric constant (epsilon') and the loss factor (epsilon `') for the thick films were measured by VSWR slotted section method in the 8-18 GHz range of frequencies. Microwave attenuation properties were studied using a waveguide reflectometer set up. Findings - Both the epsilon' and epsilon `' were found to vary with frequency and composition x It is observed that, value of epsilon' increases with increase in x, due to the increase in bulk density and reduction in porosity of the material, that resulted due to the substitution of cobalt in Ni-Zn ferrite. The microwave transmission loss offered by the thick films was found to increase with the increase in cobalt concentration x Within the band width of 4 GHz (from 12-16 GHz), all the films except that with x = 0.04 offered the reflection loss of less than 3 dB. Originality/value - The dielectric constant of Ni0.7-xCoxZn0.3Fe2O4 thick films have been reported for the first time. These thick films provide scope for cost effective planar ferrite devices.
Keywords: Microwaves; Oxides; Thick-film circuits

Cobalt nanoparticles doped emaraldine salt of polyaniline: a promising room temperature magnetic semiconductor - Hatamie, Shadie; Kulkarni, M. V.; Kulkarni, S. D.; Ningthoujam, R. S.; Vatsa, R. K.; Kale, Sangeeta N. (Journal of Magnetism and Magnetic Materials, 2010)
Incorporation of magnetic nanoparticles in polymers with organic functional groups working as semiconducting substrate is of immense interest in the field of dilute magnetic semiconductors (DMS) and spintronics. In this article we report on synthesis and evaluation of dilutely doped (0-10 wt%) cobalt nanoparticles in emaraldine salt (ES) of polyaniline in the presence of dodecyl benzene sulfonic acid (DBSA) and p-toluene sulfonic acid (p-TSA) using a sonochemical-assisted-reduction approach as a possible DMS candidate. The X-ray diffraction pattern and high resolution transmission electron microscopy (HRTEM) image show the ES to be polycrystalline, in which 10 nm sized Co nanoparticles get embedded in its FCC structural form. From Fourier transform infrared (FT-IR) and UV-visible (UV-vis) spectroscopy studies, it is predicted that cobalt particles get electrostatically bound to the specific SO(3)(-) ion sites of ES, thereby modifying torsional degrees of freedom of the system. The applied field dependent magnetization study shows that the sample exhibits hysteresis loop with a minimal doping of 3 wt% of Co nanoparticles and increases with the amount of Co nanoparticles in ES due to dipolar interaction. The electron transport data show that with increase in Co wt% there is a gradual shift from ohmic to non-ohmic response to the sample bias, accompanied by opening of electrical hysteresis and an increased resistance. The non-linear response of higher doped systems has been attributed to the combination of direct and Fowler-Nordheim tunneling phenomena in these systems. Persistence of optical and transport properties of the polymer, with an introduction of magnetic moment in the system, envisages the system to be a fine magnetic semiconductor. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Cobalt nanoparticles; Magnetic semiconductor; polyaniline

Influence of Mg2+ substitution on the magnetic and electrical properties of Li-Zn ferrite thick films synthesized with PVA matrix - Rendale, M. K.; Kulkarni, S. D.; Kulkarni, D. C.; Puri, Vijaya (Microelectronics International, 2011)
Purpose - The purpose of this paper is to investigate the effect of Mg2+ substitution on the magnetic and electrical properties of Li0.35-x Mg-2x Zn-0.3 Fe2.35-xO4 thick films synthesized with polyvinyl alcohol (PVA) matrix. Design/methodology/approach - The nanoferrites Li0.35-x Mg-2x Zn-0.3 Fe2.35-xO4 (x = 0, 0.07, 0.14, 0.21, 0.28 and 0.35) were synthesized by chemical technique using aqueous solution of PVA (the matrix) and thick films were fabricated by screen printing technique. The DC magnetic hysteresis measurements, AC magnetic susceptibility and DC electrical resistivity were measured as a function of temperature. Findings - The lattice parameter of thick film Li0.35-x Mg-2x Zn-0.3 Fe2.35-xO4 (x = 0, 0.07, 0.14, 0.21, 0.28 and 0.35) increases with the substitution of Mg2+ ions for Li1+ and Fe3+. The surface morphology of the thick films showed the grain size increasing with Mg2+ substitution till x = 0.21 and then decreasing for the higher concentrations of magnesium. The magnetic moment n(B) (mu(B)) computed from the M-s obtained by extrapolation of the magnetization curve showed a gradual decrease with the composition till x = 0.21, beyond which a sudden decrease was observed. The resistivity of the films at room temperature had variation with composition x, similar to that of magnetic moment. The activation energies Delta E-F and Delta E-P were found to vary with composition x of the ferrite system. Originality/value - The paper reports, for the first time, the magnetic and electrical properties of fritless Li0.35-xMg2xZn0.3Fe2.35-xO4 thick films using PVA polymer matrix. Up to x = 0.21 (Mg2+), grain size increases and Curie temperature decreases beyond which reverse effect takes place.
Keywords: Alternating current; Direct current; Electrical properties; Films (states of matter); Magnetic moments

Effect of cation distribution on structural and magnetic properties of Dy substituted magnesium ferrite - Bamzai, K. K.; Kour, Gurbinder; Kaur, Balwinder; Kulkarni, S. D. (Journal of Magnetism and Magnetic Materials, 2013)
Magnesium ferrite and dysprosium (Dy3+) substituted with composition MgDyxFe2-xO4 (x = 0.00-0.07) was prepared by solid state reaction technique. Spinel phase formation was identified using x-ray diffraction technique, thus establishing the cubic spinel symmetry. The morphology was seen through scanning electron microscopic technique, from where the grain size was calculated using average intercept line method. The elemental composition of pure and dysprosium substituted magnesium ferrite was calculated from energy dispersive x-ray analysis spectrum which is then correlated with the experimentally obtained values. Magnetic hysteresis loop of the various compositions establishes it to be soft ferrimagnetic material. The magnetic parameters such as saturation magnetization, coercivity, and retentivity were also calculated. Temperature dependence of saturation magnetization was done to find the Curie temperature of different compositions. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Cation distribution; Curie temperature; Electron microscopy; Magnetization; Spinel ferrite

Ru-TiO2 semiconducting nanoparticles for the photo-catalytic degradation of bromothymol blue - Kulkarni, R. M.; Malladi, R. S.; Hanagadakar, M. S.; Doddamani, M. R.; Santhakumari, B.; Kulkarni, S. D. (Journal of Materials Science-Materials in Electronics, 2016)
Photo-catalytic degradation of bromothymol blue (BTB) in an aqueous medium by Ru-TiO2 using UVC (254 nm) irradiation was investigated for a pH range of 4.0-8.0. The liquid impregnation method was used to synthesize 0.2, 0.4 and 0.8 % ruthenium doped TiO2 (Ru-TiO2) nanoparticles. The characterizations of resulting nanoparticles were done using X-ray diffraction, scanning electron microscopy, fourier transform infrared spectroscopy, transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy analysis. The crystallite sizes of doped and undoped nanoparticles were determined from X-ray diffraction spectra using Scherrer equation. The average crystallite size of undoped TiO2 was found to be 17.00 nm, whereas the crystallite sizes of 0.2, 0.4 and 0.8 % Ru-TiO2 were 16.67, 15.70 and 14.40 nm respectively. The TEM images confirm the particle sizes to be 10-40 nm. Pseudo-first order rate constants (k(obs)) determined were found to decrease with increase in pH. The effect of BTB Concentration, catalyst dosage, a percentage of doping of photo catalyst, pH and UV light intensity of BTB on the degradation rate were also examined.